2011
DOI: 10.1146/annurev-genom-082410-101451
|View full text |Cite
|
Sign up to set email alerts
|

Putting Medical Genetics into Practice

Abstract: This article describes a fragment of history on the growing impact of genetics on the practice of medicine over 50 years, as experienced by a medical geneticist who helped to provide services to patients at risk of genetic disorders. It is a personal account influenced by a fascination with chromosomes that has drawn him into many studies, including sex determination, gene discovery, fetal diagnosis, phylogenomics, and karyotype evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…My interest in KS is detailed more fully elsewhere (Ferguson‐Smith, 2011) but a brief outline may be appropriate here. I had been a trainee pathologist at Glasgow University and, in 1956–1957 with Bernard Lennox, a high frequency of KS at an infertility clinic was discovered (Ferguson‐Smith et al, 1957).…”
Section: Figurementioning
confidence: 99%
“…My interest in KS is detailed more fully elsewhere (Ferguson‐Smith, 2011) but a brief outline may be appropriate here. I had been a trainee pathologist at Glasgow University and, in 1956–1957 with Bernard Lennox, a high frequency of KS at an infertility clinic was discovered (Ferguson‐Smith et al, 1957).…”
Section: Figurementioning
confidence: 99%
“…Many of the mutations in the apolipoprotein B gene alter the functional activity of the protein and reduce the binding of LDLr and delay the removel of LDL moleculas and thus the accumulation of Cholesterol in the circulatory system, so far, four mutations have been identified that cause Familial Defective apolipoprotein B (FDB) the LDL-r link in the apoB gene is: R3480W, R3500Q, R3500W and R3531C [15]. The CGG-CAG in amino acid code 3500 led to the replacement of glutamine to arginine (R3500Q) the most common change which causes FDB [16]. the results in a change in function of the apoB gene, which in turn results in an increase in hypercholesterolemia with an increased risk of atherosclerosis [14,15].…”
Section: Specific-primer -Pcrmentioning
confidence: 99%
“…group [16] In their study of 30 Iranian people in Chaharmal in Bakhtiari province south western Iran, who were likely to have (FH) , the disease was clinically diagnosed the aim of their study was to study the properties of the LDLR gene and three common gene mutations of the apoB gene secondary causes of high Cholesterol, such as Diabetes, Hypertension, Smoking habits and family history had Coronary Artery Disease.…”
mentioning
confidence: 99%
“…Chromosome painting with whole chromosome-specific DNA probes reveals these domains as distinct chromatin territories equivalent to the number of chromosomes. The observation of six chromatin territories, corresponding to a diploid number of six, that fill the interphase nucleus of the Indian muntjac is a dramatic early example observed in 1994 [ 29 ] and illustrated later [ 30 ]. After DNA replication the chromatin loops are gathered towards their attachment sites and, as prophase advances, the chromomeres reform so that at metaphase the chromatids once more become cylindrical.…”
Section: Introductionmentioning
confidence: 99%